The Political Ecology of the Modern Peasant Calculation and Community (Johns Hopkins University Press, 1994)
Does political action by peasants primarily serve the interests of the individual or does it address community concerns as well? Previous attempts to resolve this question often became mired in the age-old debate over selfish versus altruistic behavior. In The Political Ecology of the Modern Peasant, Leslie Anderson goes beyond the polarized positions of earlier discussions to reach a new synthesis in which individual and community interests are shown to be both interdependent and mutually sustaining. Drawing on a wealth of personal experience in villages of Costa Rica and Nicaragua, Anderson puts forth a theory with broad implications for the study of peasant political behavior in Latin America and throughout the Third World. The Political Ecology of the Modern Peasant will be of interest not only to political scientists but also to anthropologists, sociologists, and students of developing countries and Latin America.